“Dragons – in the Crease”: The Many Masks of Emily Dickinson - Marinela Freitas, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
ABSTRACT: This article examines the multiplicity of masks in Emily Dickinson’s poetry, focusing on her strategies of concealment and revelation through tropes of the veil, the dragon, and the volcano. By situating Dickinson within the Victorian dramatic tradition and the cultural expectations imposed upon nineteenth-century American women writers, the analysis highlights her slant poetics as a means of negotiating identity, authority, and desire. Dickinson’s poetic selves often emerge as armored bodies – simultaneously reticent and explosive, veiled and volcanic – whose vitality is dramatized through recurrent figurations of fire, ice, storm, and eruption. The essay argues that Dickinson’s art lies in this poetics of excess, where silence and obliquity become performative strategies that exceed the constraints of gender and culture.